DETERMINANTS OF YOUTH’S POLITICAL NEWS CONSUMPTION ON SOCIAL MEDIA: A TECHNOLOGY ACCEPTANCE MODEL PERSPECTIVE - Muralidharan Kannan, Muralidharan.K; R, Jayaseelan; S, Kadeswaran; D, Soundra Rajan; K S, Chithra Lekshmi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In the digital era, the manner in which individuals access political information has undergone significant transformation, with social media platforms emerging as the primary source for individuals aged 18–30 years. This study employs an expanded technology acceptance model (TAM) to investigate how factors, such as perceived usefulness, perceived ease of use, trust in platforms, and digital literacy, influence the political news consumption habits of young users in Coimbatore, Tamil Nadu, India. Utilizing a quantitative cross-sectional survey involving 250 participants from this region, the research examines the relationships between these elements and behavioral intentions related to political engagement on social media. The principal findings reveal that perceived usefulness (β = 0.42, p < .001) and trust (β = 0.31, p < .01) are significant predictors of behavioral intention, whereas digital literacy moderates the impact of ease of use on intention and consumption. Furthermore, perceived ease of use enhances perceptions of usefulness, aligning with TAM extensions in digital contexts. These findings underscore the role of social media in fostering civic participation, despite challenges, such as misinformation and echo chambers, particularly in a linguistically and culturally diverse region, such as Tamil Nadu. Theoretically, the study extends TAM by integrating trust and literacy into political communication. Practically, it provides insights for media outlets, educators, and policymakers to promote responsible consumption and counteract disinformation. Limitations include the cross-sectional design and focus on urban youth in Coimbatore, suggesting opportunities for longitudinal and comparative research. Overall, this research contributes to understanding youth digital behaviors in democratic processes and emphasizes the necessity for targeted interventions to promote informed political discourse.